Tracey judgement and hospice DNACPR orders: steady as she goes or seismic change?. Issue 4 (25th July 2018) - Macfarlane, Michael; Shayler, Stephanie; Nelms, Louisa; Willis, Derek
Abstract : Objectives: The 2014 Court of Appeals decision with respect to Tracey vs Cambridge University Hospital ('the Tracey judgement') changed the requirements for discussing Do Not Attempt Cardiopulmonary Resuscitation (DNACPR) decisions with patients. This study is a retrospective case note review aiming to identify any changes in practice around discussing DNACPR decisions in hospices following the judgement. Methods: 150 case notes from 2013 (before the Tracey judgement) were compared with 150 case notes from 2015 (following the Tracey judgement). These notes came from five hospices in the West Midlands. The notes were analysed to determine if the judgement resulted in changes to how frequently DNACPR decisions were discussed with patients and their families, as well as whether there were any changes in the documentation of reasons for not discussing such decisions. Results: Discussions with patients around DNACPR decisions increased from 31% to 60% and with relatives from 29% to 59% following the Tracey judgement. Prior to the judgement the most frequently documented reason for not discussing was to avoid distress (23%), whereas after judgement it was patients lacking capacity to engage in such a discussion (40%). There was a lack of consistency and clarity in defining the concept of 'physical or psychological harm'. Conclusions: Although DNACPR decisions are being discussed more frequently with patients and families following the Tracey judgement, clarity on what constitutes 'physical or psychological harm' caused by these discussions is still required. Future research must examine whether the judgement is delaying or preventing DNACPR decisions being made.